Seismic Geomorphological Analysis of Late Miocene Sequences, Offshore Sabah Basin - Qi Ngui, J. (2019)
Seismic geomorphology is a rapidly emerging discipline that facilitates the study of subsurface. It is developed as an integration of different analytical techniques to examine the buried landforms (geomorphological feature) using seismic data. This study attempted to analyze the seismic geomorphology of a set of 3D (three-dimensional) offshore seismic data. In the case study, 3D seismic data from the Y Field is interpreted to display the sequence stratigraphy, sedimentary features and bodies of the Miocene deposits. Representative and successive horizons which bear imprints of the geomorphologic evolution are interpreted and picked through the 3D volume before extracting the amplitude attribute map. The time slices, amplitude map and attribute extractions infer lithologic changes as it plots the strength of reflection wavelet on the seismic data. Similar geomorphic features are grouped together as each depositional element displays different morphology and seismic expression. Seismic geomorphological analysis leads to the mapping and visualization of depositional elements and significant features. In this study, the progradational deltaic environment is analyzed and discussed. Â© 2018 SEG.